Marital Property Regime in North Macedonia and in Kosovo - Alishani Sopi, Detrina (Faculty of Law, Ss. Cyril and Methodius University, Skopje, 2021)
Despite the fact that marital law is one of the most important institutes of family law, this institute should be regulated in the best possible way. But this has not happened, because there are still many legal gaps and uncertainties in the regulation of this institute. These legal gaps are mostly presented in the regulation of property relations between spouses, presenting problems in the application of these provisions in court practice. The marriage has the effect in creating property relations between the spouses and their regulation is inevitable and on the other hand, the better these relations are regulated, the less problems the spouses will have in the event of the termination of the marriage. It is obvious that the regulation of property relations between spouses has not been the focus of the legislator because the laws issued in North Macedonia and Kosovo were issued many years ago, when the number of divorces was not very high. But with the change of economic relations of the market and with the emancipation of women this number is increasing and the demand for the regulation of property relations is increasing. For this reason, through this paper, legal gaps will be identified and recommendations for their improvement will be given. These recommendations will be given by making an in-depth analysis of the laws that regulate property relations between spouses in North Macedonia and Kosovo and their application in practice on the one hand while on the other hand a comparison will be made with several countries of Europe and USA. The methodology that will be used in this paper will be historical, analytical and comparative methods. From the analysis made and comparison with other countries of the world we will give recommendations for the improvement of the legal infrastructure. Above all the recommendations will be given in the importance of legal regulation of the family house which does not enjoy the necessary protection and the importance of incorporating the marriage contract in legislation, as an alternative for spouses to autonomously regulate their property relations.
Докторска дисертација одбранета во 2021 година на Филолошкиот факултет во Скопје, под менторство на проф. д–р Ангел Ристов.